Implementasi Kewirausahaan Berbasis Proyek Bagi Mahasiswa FKIPK IAKN Palangka Raya - Johnson Wadani; Lara Lara; Risa Risa; Siska Pranika; Defri Triadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Entrepreneurship is an activity that until now has a positive value for economic development in Indonesia. Based on BPS data in the last 3 years (2021, 2022, and 2023), the decline in the unemployment rate continues to increase. Thus, the research aims to see how the implementation of project-based entrepreneurship is carried out by students. On the basis of his thinking, these entrepreneurial activities can help make students more creative, innovative, independent and help improve the Indonesian economy. This research is a qualitative type with a descriptive qualitative approach. Data collection in this study uses observation, interview, and documentation techniques. The results of the study show that the implementation of project-based entrepreneurship for students of the Faculty of Teacher Training and Christian Education (FKIPK) IAKN Palangka is an activity that is in line with a project-based learning theory which has been widely carried out in secondary schools. The impact of the implementation of project-based entrepreneurship for students of the Faculty of Teacher Training and Christian Education (FKIPK) IAKN Palangka Raya includes negative and positive sides. The negative side is that it is difficult for students to divide their time between project work and lecture activities. Meanwhile, the positive side of the implementation of project-based entrepreneurship provides experience, insight, entrepreneurial abilities and skills, as well as the growth of students' interest in entrepreneurship in a creative, innovative, and independent manner.